2008
DOI: 10.1007/s00280-008-0885-5
|View full text |Cite
|
Sign up to set email alerts
|

Fixed-dose rate infusion of gemcitabine and weekly cisplatin in elderly or poor performance status patients with unresectable non-small cell lung cancer

Abstract: Our results indicate that this regimen is a feasible treatment for elderly or poor performance status patients with unresectable NSCLC. Nevertheless, the morbidity due to myelosuppression and infection following this treatment should be carefully considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Because the total dose of cisplatin is similar, this treatment can significantly reduce the incidence of renal toxicity and improve the completion rate of chemotherapy cycle. 20,35 Comparing the administration of 30-40 mg/m 2 cisplatin for 3 consecutive days (A1) with 80-120 mg/m 2 cisplatin for only 1 day (A2) to elderly patients (both A1 and A2 were given hydration), the results showed that the incidence of grade III/ IV renal damage in A2 (15.4%) was significantly higher than that in A1 (2.5%). 29 The incidence of cisplatin-induced renal toxicity varies greatly among different types of tumors due to the different chemotherapy regimens, initial doses, and accumulated doses used.…”
Section: Incidence Of Cisplatin-related Renal Toxicity In Elderly Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the total dose of cisplatin is similar, this treatment can significantly reduce the incidence of renal toxicity and improve the completion rate of chemotherapy cycle. 20,35 Comparing the administration of 30-40 mg/m 2 cisplatin for 3 consecutive days (A1) with 80-120 mg/m 2 cisplatin for only 1 day (A2) to elderly patients (both A1 and A2 were given hydration), the results showed that the incidence of grade III/ IV renal damage in A2 (15.4%) was significantly higher than that in A1 (2.5%). 29 The incidence of cisplatin-induced renal toxicity varies greatly among different types of tumors due to the different chemotherapy regimens, initial doses, and accumulated doses used.…”
Section: Incidence Of Cisplatin-related Renal Toxicity In Elderly Patientsmentioning
confidence: 99%
“…This regimen has the same efficacy and less nephrotoxicity than a one-time high dose regimen. 20,35,36,69 In Ohe’s study, elderly (⩾75 years) patients with NSCLC were given chemotherapy consisting of 25 mg/m 2 cisplatin on days 1, 8, and 15. A small dose of hydration therapy was given (1500 ml of normal saline).…”
Section: Risk Factors For Cisplatin-induced Renal Toxicity In Elderly...mentioning
confidence: 99%